Stem Cell Therapy in Children With Sensorineural Hearing Loss: A Narrative Review - Mahbobeh Oroei; Mohsen Ahadi (Mazandaran University of Medical Sciences, 2021)
Context: One of the research areas is using stem cell transplantation for treating children's sensorineural hearing loss. Preclinical studies and testing of the stem cell types have been performed in this field, and relative improvement has been achieved. Objectives: This narrative review has been prepared to study the advancements in hearing regeneration with stem cell transplantation. Data Sources: The English articles with full-text were searched in PubMed, Scopus, and Google scholar from 2000 to 2020 using keywords of sensory neural hearing loss and stem cell. Results: In 2018, the first human study was performed with stem cells from the human umbilical cord, which has promising results regarding the safety of the method and its positive effects on hearing. Conclusions: Autologous stem cell transplantation had induced relative improvement without serious adverse events in children with acquired sensorineural hearing loss. To obtain more evidence, further studies are required with larger sample sizes and in different patients groups.